2010
DOI: 10.1099/mic.0.036095-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of, and in vivo stressosome formation by, single members of the RsbR protein family in Bacillus subtilis

Abstract: The Bacillus subtilis stressosome is a 1.8 MDa complex that is the focal point for activating the bacterium's general response to physical stress. In vitro studies demonstrated that the stressosome's core element can be formed from one or more of a family of paralogous proteins (RsbRA, -RB, -RC and -RD) onto which the system's activator protein (RsbT) and its principal inhibitor (RsbS) are bound. The RsbR components of the stressosome are envisioned to be the initial receptors of stress signalling with the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 40 publications
1
31
2
Order By: Relevance
“…3D). The latter observation might be explained by a lower expression level of rsbRD, as has recently been suggested (35), although our Western blot does not suggest large differences in protein concentration. However, despite the minor roles of RsbRC and RsbRD, the additional presence of either one allows RsbRA to overcome the negative effect of RsbRB (Fig.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…3D). The latter observation might be explained by a lower expression level of rsbRD, as has recently been suggested (35), although our Western blot does not suggest large differences in protein concentration. However, despite the minor roles of RsbRC and RsbRD, the additional presence of either one allows RsbRA to overcome the negative effect of RsbRB (Fig.…”
Section: Discussioncontrasting
confidence: 44%
“…6) (23), again indicating normal functionality of the stressosomes. Third, a recent study found the expression levels of rsbRA and rsbRB to be similar (35). The availability of sufficient protein is also suggested by the Western blot shown in Fig.…”
Section: Discussionmentioning
confidence: 75%
“…S8). For example, it was reported that RsbT could become unstable once released from the stressosome, which would prevent the system from maintaining a strong activation level after a step increase in stress (47). Activation of σ B requires an element that can transduce the total level of stress rapidly enough to "outrun" this negative feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and biochemical studies have shown that the B. subtilis stressosome comprises at least three protein species: the RsbT serine/threonine kinase, the RsbS antagonist, and one or more members of the RsbR coantagonist family (1,9,13,24,32). In vivo each stressosome appears to contain a mixture of the four partially redundant RsbR coantagonists, RsbRA, RsbRB, RsbRC, and RsbRD, and in vitro these coantagonists can dynamically exchange into the complex (13,24).…”
mentioning
confidence: 99%